FPGA Based Data Hiding Methods using DNA Cryptography Techniques - B. Murali Krishna; CH. Surendra; K. Mani Varma; K. Mani Kanta; S.K. Shabbeer; G.L. Madhumati (Institute of Advanced Engineering and Science, 2016)
To convey the information safely DNA grouping mechanisms are used. There are many methods used by DNA sequences. The proposed method is of both encryption and information concealing utilizing a few properties of Deoxyribonucleic Acid (DNA) groupings. This technique is highlighted that DNA groupings have many more intriguing properties which are used for concealing the information. There are three strategies in this encryption strategy: the Insertion Technique, the Complimentary Pair Technique and the Substitution Strategy .For every single strategy, a specific reference DNA grouping P is chosen and then the taken sequence is changed over with the mystery message M and is consolidated, so that P0 is acquired. P0 is then sent to the collector and the beneficiary can recognize and separate the message M covered up in P. This technique is proposed to utilize INSERTION Strategy. Subsequently, the proposed plan comprises for the most part of two stages. In the principal stage, the mystery information is encoded utilizing a DNA Sequence. In the second stage the encoded information is steganographically covered up into some reference DNA grouping utilizing an insertion strategy. The effectiveness of this security algorithm is seen with many merits and limitations. A, C, G, and T are the 4 nucleotides which are taken for this project.